Investigating the relationship between language learning anxieties and strategies in a Malaysian TVET / Adibah Halilah Abd Mutalib - Abd Mutalib, Adibah Halilah (2015)
It has long been discovered that a subdued amount of anxiety is felt by the language learner. Such anxiety can in turn lead to positive; facilitating anxiety, or may result in debilitating anxiety. Many studies have focused on the effects of language anxiety on academic performance and proficiency level, but few studies have focused on the relationship between language learning anxiety and strategies used. Thus, in an attempt to unravel some of the language learning anxiety most commonly found among learners, this study will investigate the link between language anxiety and strategy use in an English language course. The participants of this study comprised of 132 students currently enrolled in their third semester of an engineering diploma programme in a Malaysian Technical and Vocational Education and Training (TVET) centre. The study employed three survey instruments; the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz et al (1986) to measure language anxiety, the Strategy Inventory for language learning (SILL) designed by Oxford (1990) to look into language learning strategies and finally Coping strategy inventory (CSI) developed by Tobin (1984) to assess coping strategies used . In general, the study revealed a significant difference between low and high language anxiety learners where both groups indicated a high anxiety level for the subscale fear of negative evaluation. It was discovered that even though affective strategy was dominant in both the high and low language anxiety groups; a t-test revealed that only cognitive, memory and metacognitive language learning strategies showed a significant difference between the two groups. Further to that, the research showed that between high and low language anxiety groups, there was no meaningful association in terms of language learning strategies used which implies that there is no strong link between levels of anxieties and language learning strategies practiced. With respect to language learning anxiety and coping strategies, it was seen that both high and low-anxiety learners exhibited a strong tendency to express emotions when faced with language anxiety. Via a t-test, the findings showed a significant difference between levels of language anxiety and all coping strategies practiced; except for self-criticism. Nonetheless, with stronger association seen in social withdrawal and problem avoidance strategies, the low-anxious learners provided evidence that ‘disengagement’ was the strategy of choice when faced with language anxiety. This research discusses the links between language anxiety and strategies used, and concludes with recommendations and implications for teaching and research that recognize language learning anxiety.